The Influence of School Culture on the Readiness of Accounting Graduates for the CPA Licensure Examination - Roda, Frederick; Villagonzalo, Benjamin Jr.; Almacin, Kyla Marie; Aranza, April Roween; Mogar, Ria Melcah (Journal of Interdisciplinary Perspectives, 2025)
This research explores the role of school culture in shaping Accountancy graduates' readiness for the Certified Public Accountant Licensure Examination (CPALE), addressing the historically low passing rates (e.g., 16.46% in May 2019, 14.32% in October 2019, and 25.84% in October 2022). Guided by Schein's Organizational Culture Framework (2010), the study investigates how dimensions of school culture, such as social, intellectual, and economic climates, institutional rules, policies, and values, affect CPALE preparedness. A quantitative design was employed, with data collected from 34 Accountancy graduates (selected through purposive sampling from private and public schools). Statistical tests, including the t-test and ANOVA, revealed significant differences in school culture perceptions between private and public school graduates, with a t-value of 3.21 (p < 0.05). Graduates from private schools reported higher scores in intellectual climate (4.2) and social climate (4.0) compared to their public-school counterparts (3.8 and 3.7, respectively). The findings indicate that school culture influences the readiness of Accountancy graduates for the CPALE, with Social Climate scoring a weighted mean of 3.8950, Intellectual Climate scoring 3.8361, and Economic Climate scoring 3.4622, reflecting a general agreement among respondents. These findings suggest that a supportive intellectual and social environment enhances graduates' preparedness for the CPALE. Based on these results, the study recommends that schools, particularly public institutions, improve faculty training, clarify policies, and increase resources to support CPALE success better and ultimately improve pass rates.